Fabrication of Aluminium Matrix Composite Powder Reinforced with Silicon Dioxide Tailings for Non-Asbestos Brake Pads (NOB) - Sukanto Sukanto; Ilham Ary Wahyudie; Erwanto Erwanto; Yudi Oktriadi; Rodika Rodika; Ricky Irwansyah; Husman Husman; Devrin Dwiki Saputra; Haradat Tahrir Algaza (Jurnal Penelitian Pendidikan IPA, 2024)
Tin mining tailings consist of 80-90% sand and the rest mud.  The high levels of Silicon Dioxide (SiO2) in these tailings are hard and can be used as an added material in the manufacture of composites.  This research aims to study the physical and mechanical properties of metal matrix composites reinforced with SiO2 powder processed by powder metallurgy, as an effort to provide a replacement material for Non-Asbestos (NOB) motorbike brake linings.  The impact of hot compaction pressure in the form of two pressing directions, including 4600, 4500 and 4400 Psi, with a pressing hold of 15 minutes and sintering which includes 30, 20 and 10 minutes, at a temperature of 600 ºC was studied for its effect on hardness and density.  Mechanical blending was used with a horizontal ball mill in the ratio of 10:1 at a speed of 90 rpm for 4 hours.  The test results showed that the greater the hot compaction pressure and the longer the sintering, the higher the hardness and density values.  The highest hardness reached 81.7 HB and the highest density of 2.385 g/cm3 occurred at a bidirectional hot compaction pressure of 4600 Psi, with the lowest wear rate of 0.333 mm3/m. This occurs as a result of the increase in hot compaction has an impact on increasing the contact between powder particles resulting from mechanical alloying to be tighter as a result of which the cavity and porosity decrease